Ice hockey stick and puck biomechanical predictors of wrist shot accuracy - Michaud-Paquette, Y. (Department of Kinesiology and Physical Education, McGill University, 2008)
The purpose of this study was to identify the movement patterns of the ice hockey stick from a wrist shot that corresponds to the accuracy of puck trajectory. A total of twenty five subjects participated in this study; each performed 10 successful wrist shots on four targets. Performances were evaluated by simultaneously recording the movements of the stick's shaft and blade and of the puck with infra-red based motion capture (Vicon®) system (240 Hz) Kinematics of the shaft and blade of the hockey stick were examined using a multiple regression analysis using the accuracy score as the dependant variable. The results indicate that accurate shooters tended to alter release parameters (puck release orientation and velocity), loading mechanics and blade orientation to achieve proper puck trajectory explaining 40% and 76% of the accuracy variances for the bottom and top corners respectively. Shooters were more accurate shooting at bottom corners than at the top corners (67% vs 45%). These analyses helped to identify key stick usage variables that predict accuracy during the execution of stationary wrist shots. Further studies are needed to identify the whole body kinematic patterns associated with the hockey stick kinematics.